2020
DOI: 10.3389/fpsyt.2020.572530
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Victimization and Adolescent Drinking Behavior: Deviant Peer Affiliation as a Mediator and Personal Growth Initiative as a Moderator

Abstract: Research has demonstrated a robust positive association between cyberbullying victimization and adolescent drinking behavior; however, the mediating and moderating mechanisms underlying this relationship remain largely unexplored. Grounded in the social development model and person-environment interactions model, our study explored whether deviant peer affiliation mediated the relationship between cyberbullying victimization and adolescent drinking behavior and whether this mediating effect was moderated by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Firstly, consistent with previous findings, our results showed that cyber-victimization was positively correlated with tobacco and alcohol use among elementary, middle, and high school students [22,27]. This may suggest that after being cyberbullied, children and adolescents may adopt negative or even self-medicating strategies (tobacco and alcohol use) to cope with the distress caused by victimization [37,38].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Firstly, consistent with previous findings, our results showed that cyber-victimization was positively correlated with tobacco and alcohol use among elementary, middle, and high school students [22,27]. This may suggest that after being cyberbullied, children and adolescents may adopt negative or even self-medicating strategies (tobacco and alcohol use) to cope with the distress caused by victimization [37,38].…”
Section: Discussionsupporting
confidence: 91%
“…For elementary school students, apart from their family members, they may be less exposed to tobacco and alcohol, and deviant peers may represent one of their "windows" for exposure to cigarettes and alcohols [39]. The model role of deviant peers enhances their positive attitude towards and potential engagement in similar behaviors [27,42]. Therefore, when elementary school students who have affiliated with deviant peers experience cyber-victimization, they are likely to smoke and drink to cope with this interpersonal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, deviant peer affiliation may mediate the relationship between perceived discrimination and IGA. Several studies have indicated that deviant peer affiliation mediates negative interpersonal interactions and problem behaviors [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, adolescents who perceive discrimination or unfair treatment from the mainstream peer group may seek emotional support from other alternative groups, such as deviant youths who are also rejected by the mainstream peer group [ 16 ]. For example, Brody et al [ 17 ] found that perceived discrimination predicts greater affiliations with substance-using peers and, in turn, greater substance use.…”
Section: Introductionmentioning
confidence: 99%